Risk factors and features of COVID-19 course in pregnant women: a comparative analysis of epidemic outbreaks in 2020 and 2021 - Tatiana E. Belokrinitskaya; Nataly I. Frolova; Kristina A. Kolmakova; Evgeniya A. Shametova (IP Berlin A.V., 2021)
Aim. To compare risk factors, features of COVID-19 course and outcomes in pregnant women during epidemic increase in incidence in 2020 and 2021. Materials and methods. The study included 163 pregnant women with laboratory-confirmed SARS-CoV-2 infection within May December 2020 (1st2nd waves of the epidemic) and 158 pregnant women who had new coronavirus infection within May August 2021 (3rd wave of the epidemic). Patients in all groups were comparable in age (1835 years), social status, parity, body mass index, and had no known risk factors for COVID-19. Results. Iron deficiency anemia, smoking, belonging to the Buryat ethnic group were recognized as persistent risk factors for COVID-19 in pregnant women. Over the 1st year of the pandemic, in pregnant women, the following clinical manifestations of novel coronavirus infection were commonly seen: anosmia (87.7%), somnolence (68.7%), shortness of breath even with a mild lung damage (68.1%). In the 3rd wave of the 2nd year of the pandemic, the leading signs and symptoms were cough (70.3% vs 38.7%, p0.001), runny nose (46.2% vs 3.7%, p0001), sore throat (367% vs 37%, p0.001); an increase in body temperature above 38C (19.6% vs 7,4%, p=0.006), pneumonia detected by computed tomography (61.4% vs 21.4%; p0.001). There was a significant increase in the incidence of severe lung lesions (with computed tomography 34: 17.7% vs 4.9%; p0.001) and admissions to intensive care units (11.4% vs 6.4%; p= 0041). There was a need for invasive mechanical ventilation (1.89% vs 0%; p=0.118). There was 1 death (0.63% vs 0%; p= 0.492), which was associated with the fulminant course of COVID-19. Conclusion. Persistent COVID-19 confounders in pregnant women who have no known risk factors in the third trimester of gestation are iron deficiency anemia, smoking, and belonging to the Buryat ethnic group. The clinical course of SARS-CoV-2 infection has changed and became more unfavorable: symptoms of acute respiratory disease (cough, runny nose, sore throat) began to prevail, the rate and severity of pneumonia and rate of mortality increased.